Caracterización de las propiedades físico-químicas del suelo y elaboración de un plan de fertilización para el cultivo de papa nativa, en el sector Simón Bolívar del Sistema de Riego Aguarongo – Zañe, Parroquia Chuquiribamba - Benitez Soto, Gladys Esperanza (2024)
The study was carried out at Simón Bolívar sector of the Aguarongo-Zañe irrigation system, located in the parish of Chuquiribamba. The main land uses include the cultivation of white corn (32.64%), pasture (34.52%), leaf onion (18.25%), vegetables (6.70%) and potato (2.88%). The low levels of potato production (2.96 t/ha) are associated with low aeration capacity (5.25%) due to overgrazing, clay loam texture, high aluminum content (4.41 meq/100 ml), acid soils (pH =4.5), low nutrient content (N, P, K, B and Zn). The main objective of the research is to contribute to the increase of native potato yield through the physicochemical characterization and elaboration of a fertilization plan. During the study, unaltered soil samples were taken in duplicate using 100 cm3 Koppecky cylinders to determine bulk density, CC (pF=2 and 2.52), PMP (pF=4.2), saturation (pF=0), and soil physics were evaluated using the triangular diagram. For the chemical characterization, disturbed samples were taken at a depth of 25 cm in the study area. The results indicate that the physical condition of the soil is in the poor to medium range for slopes 0 - 8% and >25% and medium to good for slopes 8 - 25%. In the second horizon, physical conditions range from poor, medium and good on slopes of 0-8%, 8-25% and >25%, respectively. The chemical characteristics of the soils on the 0 - 8% slope have a medium acid pH, medium CEC, low OM, low base saturation; on the 8 - 25% and >25% slopes the pH is very acid, medium to low CEC, OM ranges from high to medium, the percentage of base saturation is low. A fertilization plan was elaborated with amendments of (CaO 36%, MgO 10% and SO4 26%) with doses from 1603 to 3354 kg/ ha-1, and nutrients N:126 to 152 kg ha-1, P: 65 to 79 kg ha-1, K: 244 to 247 kg ha-1, Ca: 20 kg ha-1, Mg:41 kg ha -1 and S 24 to 37 kg ha-1 from the three soil units.